2022
DOI: 10.1111/aji.13603
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy in adult‐onset dermatomyositis/polymyositis: A systematic review

Abstract: Background: Idiopathic inflammatory myopathy (IIM) in pregnancy is uncommon but may result in complications for both mother and the fetus. Aim:In this systematic review, we summarized the current literature investigating outcomes of pregnancy related to the dermatomyositis/polymyositis (DM/PM) process. Content:We searched PubMed, Embase, Cochrane Library, and Web of Science databases and included 61 studies reporting the disease course, pregnancy outcomes, and management of both pregnancy and DM/PM in the fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Some autoimmune diseases tend to improve during pregnancy; female patients with dermatomyositis have stable or improving symptoms during pregnancy and postpartum. 17 Future research is needed to evaluate whether that is the case in pregnant patients with SuS. Treatment options and management strategy are discussed in more details in a recently published review of SuS and pregnancy.…”
Section: Resultsmentioning
confidence: 99%
“…Some autoimmune diseases tend to improve during pregnancy; female patients with dermatomyositis have stable or improving symptoms during pregnancy and postpartum. 17 Future research is needed to evaluate whether that is the case in pregnant patients with SuS. Treatment options and management strategy are discussed in more details in a recently published review of SuS and pregnancy.…”
Section: Resultsmentioning
confidence: 99%
“…In more complicated circumstances, immunosuppressants such as azathioprine or mycophenolate mofetil are used as adjuvants alongside corticosteroids in nonpregnant state 26 . During pregnancy, the use of methotrexate and mycophenolate mofetil is associated with toxicity while azathioprine is proven to be relatively safe 30 . IVIG and plasma exchange are alternative options 26 .…”
Section: Discussionmentioning
confidence: 99%
“…26 During pregnancy, the use of methotrexate and mycophenolate mofetil is associated with toxicity while azathioprine is proven to be relatively safe. 30 IVIG and plasma exchange are alternative options. 26 Assessment of disease severity should be emphasized in consideration of treatment strategy.…”
Section: Referencementioning
confidence: 99%
“…Tang et al. 4 sought to summarize the current literature on pregnancy outcomes in DM and polymyositis (PM). Their systematic review identified 61 studies, the majority consisting of case reports and case series.…”
Section: Discussionmentioning
confidence: 99%